Fibroblast growth factor receptor (FGFR) alterations in squamous differentiated bladder cancer: a putative therapeutic target for a small subgroup - Baldia, Philipp H.; Maurer, Angela; Heide, Timon; Rose, Michael; Stoehr, Robert; Hartmann, Arndt; Williams, Sarah V.; Knowles, Margaret A.; Knuechel, Ruth; Gaisa, Nadine T. (Oncotarget, 2016)
Although drugable fibroblast growth factor receptor (FGFR) alterations in squamous cell carcinomas (SCC) of various entities are well known, little is known about FGFR modifications in squamous differentiated bladder cancer. Therefore, our study evaluated FGFR1-3 alterations as a putative therapeutic target in this subgroup. We analyzed 73 squamous differentiated bladder cancers (n = 10 pT2, n = 55 pT3, n = 8 pT4) for FGFR1-3 protein expression, FGFR1-3 copy number variations, FGFR3 chromosomal rearrangements (fluorescence in situ hybridization (FISH)) and FGFR3 mutations (SNapShot analysis). Only single cases displayed enhanced protein expression, most frequently FGFR3 overexpression (9.4% (6/64)). FISH showed no amplifications of FGFR1, 2 or 3. Break apart events were only slightly above the cut off in 12.1% (8/66) of cases and no FGFR3-TACC3 rearrangements could be proven by qPCR. FGFR3 mutations (p.S249C) were found in 8.5% (6/71) of tumors and were significantly associated with FGFR3 protein overexpression (p < 0.001), and unfavourable clinical outcome (p = 0.001). Our findings are consistent with the results of the TCGA data set for the "squamous-like" subtype of bladder cancer (n = 85), which revealed reduced overall expression of FGFR1 and FGFR2 in tumors compared to normal tissue, while expression of FGFR3 remained high. In the TCGA "squamous-like" subtype FGFR3 mutations were found in 4.9% and correlated with high FGFR3 RNA expression. Mutations of FGFR1 and FGFR2 were less frequent (2.4% and 1.2%). Hence, our comprehensive study provides novel insights into a subgroup of squamous differentiated bladder tumors that hold clues for novel therapeutic regimens and may benefit from FGFR3-targeted therapies.
EVALuna2:6882